2017
DOI: 10.1002/ajpa.23268
|View full text |Cite
|
Sign up to set email alerts
|

Region‐dependent patterns of trabecular bone growth in the human proximal femur: A study of 3D bone microarchitecture from early postnatal to late childhood period

Abstract: While providing quantitative data on how bone microarchitecture adapts to increasing mechanical demands occurring during the phases of locomotor maturation, the study reveals how regional anisotropy develops in the proximal femur to ensure a functional and competent bone structure. Decomposing the region-specific patterns of bone mass accrual is important in understanding skeletal adaptations to bipedalism, as well for understanding why fractures often occur location-dependent, both in pediatric and elderly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 56 publications
8
32
0
2
Order By: Relevance
“…As human specimens included in previous publications may also have died of disease and/or starvation, it seems unlikely, although remains a possibility, that health related factors contributed to this absence of high BV/TV in our sample prior to one year of age. The VOI protocol adopted in this study is similar to that of previous studies in humans (Gosman & Ketcham, 2009;Ryan & Krovitz, 2006;Ryan et al, 2017), and studies using a very different VOI protocol have found similar high BV/TV at birth in the human proximal femur (Milovanovic et al, 2017). In general, in chimpanzees there is an increase in trabecular bone robusticity (i.e.…”
Section: Ontogenetic Changes In Trabecular Structuresupporting
confidence: 67%
See 1 more Smart Citation
“…As human specimens included in previous publications may also have died of disease and/or starvation, it seems unlikely, although remains a possibility, that health related factors contributed to this absence of high BV/TV in our sample prior to one year of age. The VOI protocol adopted in this study is similar to that of previous studies in humans (Gosman & Ketcham, 2009;Ryan & Krovitz, 2006;Ryan et al, 2017), and studies using a very different VOI protocol have found similar high BV/TV at birth in the human proximal femur (Milovanovic et al, 2017). In general, in chimpanzees there is an increase in trabecular bone robusticity (i.e.…”
Section: Ontogenetic Changes In Trabecular Structuresupporting
confidence: 67%
“…In humans, there is a shared pattern of trabecular ontogeny across the proximal femur, proximal tibia and proximal humerus, with structural changes coinciding with the adoption of bipedal locomotion after one year of age (Gosman & Ketcham, 2009;Milovanovic et al, 2017;Ryan & Krovitz, 2006;Ryan et al, 2017). An increase in BV/TV, Tb.N, and DA occurs at around 1-2 years in the human proximal femur and proximal tibia, at the time of acquisition of bipedal locomotion (Gosman & Ketcham, 2009;Ryan & Krovitz, 2006), and BV/TV, Tb.Th and DA continue to increase into early adulthood in the proximal tibia (Gosman & Ketcham, 2009).…”
Section: Ontogenetic Changes In Trabecular Structurementioning
confidence: 99%
“…Although superior to the standard imaging protocol for HR‐pQCT (Tjong et al ), and to those commonly employed in micro‐CT studies investigating human trabecular bone (15–30 µm) (e.g. Acquaah et al ; Milovanovic et al ; Ryan et al ), true porosity is still underestimated and the values reported here must be considered approximate.…”
Section: Methodsmentioning
confidence: 72%
“…The use of SMI to characterize trabecular shape has recently been questioned (Salmon et al ). We argue that inter‐specimen comparisons of SMI may still be meaningful if samples share a similar bone volume fraction (Day et al ; Milovanovic et al ). Given that BV/TV does not demonstrate a significant relationship with age in our study, we retain the reporting of our SMI results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation